Midline posterior glossectomy and lingual tonsillectomy in obese and nonobese children with down syndrome: Biomarkers for success. (27th June 2016) - Propst, Evan J.; Amin, Reshma; Talwar, Natasha; Zaman, Michele; Zweerink, Allison; Blaser, Susan; Zaarour, Christian; Luginbuehl, Igor; Karsli, Cengiz; Aziza, Albert; Forrest, Christopher; Drake, James; et al.
Abstract : Objectives/Hypothesis: To examine outcomes following midline posterior glossectomy (MPG) plus lingual tonsillectomy (LT) for the treatment of significant obstructive sleep apnea (OSA) in children with Down syndrome (DS). Methods: Patients with DS who had persistent OSA following tonsillectomy and adenoidectomy (TA) and were relatively intolerant of positive airway pressure (PAP) therapy were evaluated by physical examination and sleep/CINE magnetic resonance imaging to determine the etiology of upper airway obstruction. Patients with relative macroglossia underwent MPG plus LT if required. Successful surgical outcome was defined as the resolution of OSA or the ability to tolerate PAP. Results: Thirteen children (8 male, 5 female), mean (standard deviation) age 14.2 (4.0) years underwent MPG plus LT. Fifty‐four percent of patients were obese (Body mass index [BMI] > 95th centile) and 8% were overweight (BMI 85th–95th centile) preoperatively. All patients underwent pre‐ and postoperative polysomnography. Postoperatively, the obstructive apnea‐hypopnea index fell significantly from 47.0/hour to 5.6/hour (P <.05) in normal weight individuals who did not become obese, but not in obese patients or those who became obese postoperatively. Successful surgical outcome was seen in all (N = 6) children who were normal weight or overweight preoperatively compared with none who were obese preoperatively (N = 7). Conclusion: Midline posterior glossectomy and LT are beneficial in normal weight and overweight children with DS who have persistent OSA following TA and are intolerant of PAP therapy. Obesity pre‐ or postoperatively portends a worse prognosis following MPG, suggesting that aggressive weight loss initiatives should be considered as an adjunct to surgery in this population. Level of Evidence: 4. Laryngoscope, 127:757–763, 2017